Photocatalytic conical optical fiber as well as preparation method and application thereof

By performing cone treatment on the optical fiber and loading the photocatalyst coating, the problem of uneven light effects in optical fiber reactors is solved, and the hydrogen production performance and photoenergy utilization rate of photocatalytic hydrolysis are improved.

CN119588277APending Publication Date: 2025-03-11RES INST OF XIAN JIAOTONG UNIV & SUZHOU +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411574474.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The optical fiber reactor system has the problem of uneven light effects, which leads to the supersaturation loss of the optical fiber front end light, and the amount of catalyst used at the end of the optical fiber is wasted.

Method used

The tapered region is formed by optical fiber drawing to increase the number of light reflections, and the photocatalyst coating is loaded on the cone to regulate the catalyst distribution to match the light distribution.

Benefits of technology

The hydrogen production performance of unit mass photocatalysts is improved, the catalyst usage is reduced, and the utilization rate of light energy is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588277A_ABST
    Figure CN119588277A_ABST
Patent Text Reader

Abstract

The invention discloses a photocatalytic conical optical fiber and a preparation method and application thereof.The photocatalytic conical optical fiber comprises an input part and a conical part with the optical fiber diameter gradually reduced, the conical part is provided with a photocatalyst coating and serves as a photocatalytic reaction end, light enters the optical fiber from the input part and is spread in the optical fiber, and when the light is reflected to the surface of the optical fiber at the conical part, the light is reflected to the surface of the optical fiber. The preparation method comprises the following steps: exciting a photocatalyst near a reflection point to generate a photocatalytic reaction, and in the preparation process, performing tapering treatment of thermal stretching on an optical fiber to obtain a tapered optical fiber with an input part and a tapered part; and preparing a photocatalyst suspension, and loading a photocatalyst coating on the conical part of the conical optical fiber through a physical impregnation method to obtain the photocatalytic conical optical fiber. The conical optical fiber structure can effectively increase the light reflection frequency of the conical part, light energy distribution is more concentrated, the problem that light energy received by a photocatalyst is not uniform in distribution is solved, and therefore the hydrogen production performance of the photocatalyst of unit mass is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalytic water decomposition to produce hydrogen, and in particular relates to a photocatalytic tapered optical fiber, a preparation method and application thereof. Background Art

[0002] With the growth of population and the development of global industrialization, energy crisis and environmental pollution problems are gradually intensifying. Photocatalytic technology uses solar energy to drive catalytic reactions, and can use sustainable solar energy to degrade pollutants, transform organic matter, and decompose water to produce hydrogen. It shows great potential in the fields of environmental purification and new energy, especially photocatalytic decomposition of water to produce hydrogen, which can effectively use solar energy to produce green hydrogen energy and provide an effective solution to alleviate resource depletion.

[0003] In the research of photocatalytic technology, the photocatalytic reactor system is one of the key areas. The current reactor designs can be roughly divided into suspension reactors, fixed bed reactors, fiber optic reactors and microfluidic reactors. The suspension reactor is characterized by a large contact surface between the catalyst and the reactants, which is suitable for large-scale processing; the fixed bed reactor fixes the catalyst on the substrate to facilitate the reuse of the catalyst; the fiber optic reactor uses the light conduction characteristics of the optical fiber to efficiently transmit light energy; the microfluidic reactor is suitable for efficient processing of trace reactions with its precise control and small volume advantages. These systems have their own characteristics and provide a variety of options for the application of photocatalytic technology.

[0004] In the fiber-type reactor system, the optical fiber surface is coated with a photocatalyst, and light is coupled from the side to enter the optical fiber for transmission, so the optical fiber serves as both a light transmission carrier and a photocatalyst carrier. The light transmitted in the optical fiber is emitted to the optical fiber surface to excite the photocatalyst, which can reduce the absorption and reflection of light by the reaction medium. Therefore, the fiber-type reactor has a lower light mass transfer resistance. Large-core fiber bundle reactors can be used for large-scale photocatalytic reactions, while small-core optical fibers can be coupled with microfluidic reactors to integrate sensing functions to achieve in-situ monitoring of photocatalytic reactions.

[0005] However, the optical fiber reactor system has the problem of uneven light action. As the number of reflections of the propagating light gradually increases, the light energy that excites the photocatalyst on the optical fiber surface will gradually decay. The inventors found that the evenly distributed catalyst and the unevenly distributed light cannot perfectly match, resulting in supersaturation loss of light at the front end of the optical fiber, while the light energy available to the large amount of catalyst at the end of the optical fiber is limited, which will cause waste of catalyst usage. Summary of the invention

[0006] The purpose of the present invention is to provide a photocatalytic tapered optical fiber, a preparation method and application thereof. The present invention effectively increases the number of light reflections in the tapered area through the optical fiber tapering process, while reducing the amount of catalyst used in the area with limited light distribution, improving the problem that the catalyst cannot perfectly match the unevenly distributed light, thereby improving the hydrogen production performance of the unit mass of the photocatalyst.

[0007] The technical solution of the present invention is:

[0008] The present invention provides a photocatalytic tapered optical fiber, comprising an input portion and a tapered portion where the diameter of the optical fiber gradually decreases, wherein the tapered portion is provided with a photocatalyst coating; the input portion is an optical fiber end that has not been subjected to heat stretching treatment, and the tapered portion serves as a photocatalytic reaction end, and light enters the optical fiber from the input portion and propagates inside the optical fiber, and when the light is reflected from the tapered portion to the surface of the optical fiber, the photocatalyst near the reflection point is excited to undergo a photocatalytic reaction.

[0009] When the photocatalytic tapered optical fiber is applied to photocatalytic hydrolysis to produce hydrogen, specifically, the input part is connected to a light source so that light enters the optical fiber for propagation, the tapered part is immersed in a reaction solution, the photocatalyst coating contacts the reaction solution, and after being excited by light, a photocatalytic water decomposition reaction to produce hydrogen occurs. The use of the photocatalytic tapered optical fiber helps to improve the hydrogen production performance of photocatalytic hydrolysis to produce hydrogen. The working principle is as follows: the refractive index of the photocatalyst coating is higher than the refractive index of the optical fiber, and the light propagating in the optical fiber can be reflected to the contact surface between the photocatalyst and the optical fiber and its vicinity, which can excite the photocatalyst to produce a photocatalytic reaction; because the diameter of the optical fiber gradually decreases in the tapered part of the optical fiber, the number of reflections of the incident light increases significantly, and the light energy distribution in the tapered part is more concentrated, which improves the light distribution; the limited catalyst in this area can utilize more light energy, thereby also improving the hydrogen production effect of the catalyst per unit mass.

[0010] Preferably, the maximum diameter of the tapered portion is 62.5-125 μm, the minimum diameter of the tapered portion is 7-10 μm, and the length of the tapered portion is 0.7-10 mm.

[0011] Preferably, the photocatalyst coating has a thickness of 100-500 nm and occupies 20%-100% of the surface area of ​​the tapered optical fiber.

[0012] Preferably, the photocatalyst in the photocatalyst coating is a semiconductor photocatalyst, preferably a sulfur-zinc-cadmium photocatalyst material Cd 0.5 Zn 0.5 S.

[0013] The present invention also provides a method for preparing a photocatalytic tapered optical fiber, the specific steps of which are as follows:

[0014] S1, performing a taper process of thermally stretching the optical fiber to obtain a tapered optical fiber having an input portion and a tapered portion with a gradually decreasing optical fiber diameter;

[0015] S2. Prepare a photocatalyst suspension, and load the photocatalyst coating on the tapered portion of the tapered optical fiber obtained in step S1 by a physical impregnation method to obtain a photocatalytic tapered optical fiber.

[0016] Preferably, in step S1, the specific steps of the hot-stretching taper treatment are:

[0017] (1) Take a 30-50 cm long optical fiber, peel off the coating layer of 3-5 cm in the middle area, wipe it clean with alcohol cotton, and clamp the two ends of the optical fiber on the two sliders of the guide rail. Fix one of the sliders and slide the other slider to make the clamped optical fiber slightly taut.

[0018] (2) Use a flame spray gun to burn the area where the coating is peeled off. After burning into a molten state, one end of the slider is fixed and the other end of the slider is pulled outward at a constant speed to stretch the optical fiber from the burned area until it breaks, forming a tapered structure.

[0019] Preferably, in step S2, the concentration of the photocatalyst suspension is 0.2-10 g / L, and the Cd 0.5 Zn 0.5 S powder and deionized water to prepare, in which Cd 0.5 Zn 0.5 The preparation process of S powder is:

[0020] a. Add thioacetamide to an aqueous solution of Cd(Ac)2*2H2O and Zn(Ac)2*2H2O under magnetic stirring, and stir the mixture for 15-20 min; wherein n(thioacetamide) / (n(Cd)+n(Zn)=(0.025-0.03):0.02;

[0021] b. Seal the mixed solution obtained in step a in a polytetrafluoroethylene-lined stainless steel autoclave, and heat to 160-180° C. for 24-26 hours; after cooling, centrifuge and separate the product, wash with deionized water and ethanol for 3-5 times, and dry in a vacuum oven at 60-80° C. for 5-6 hours to obtain a Cd0.5Zn0.5S powder sample.

[0022] Preferably, in step S2, the specific process of the physical impregnation method is: immersing the tapered portion of the tapered optical fiber in the photocatalyst suspension for 5-15 minutes, air-drying for 1-2 hours, and then heating at 150-200° C. for 1-2 hours.

[0023] The present invention also provides the use of the above-mentioned photocatalytic tapered optical fiber in photocatalytic water decomposition to produce hydrogen. The light source enters through the input part and finally propagates to the tapered part immersed in the reaction solution to excite the photocatalyst coating to produce a photocatalytic reaction.

[0024] Preferably, the light source is an LED light source or a laser light source with a wavelength range of 365-600nm;

[0025] The reaction solution is a photocatalytic sacrificial reagent, and the photocatalytic sacrificial reagent includes any one of a mixed solution of sodium sulfite and sodium sulfide, methanol, lactic acid, and triethanolamine.

[0026] The beneficial effects of the present invention are:

[0027] 1. The photocatalytic tapered optical fiber of the present invention adopts a tapered portion with a reduced diameter to be coated with a photocatalyst coating for photocatalytic reaction. When the incident light propagates to the tapered portion, the number of reflections increases significantly, and the light energy distribution is more concentrated. When the number of light reflections increases, the diameter of the optical fiber in the reaction area decreases, and the catalyst loading in the corresponding area also decreases accordingly. Therefore, the problem that the photocatalyst distribution and the light distribution of the optical fiber reactor cannot be perfectly matched is improved, and the hydrogen production performance of the unit mass of the photocatalyst is improved.

[0028] 2. When preparing photocatalytic tapered optical fiber, the thickness of the photocatalyst coating is relatively thin, so a lower-cost LED light source can be used instead of a laser light source and a high-power xenon lamp light source; at the same time, the distribution of the photocatalyst coating on the optical fiber surface in the tapered part can be regulated according to the concentration of the catalyst suspension used during immersion. When the optical fiber surface is not fully covered by the catalyst coating, the incident light can generate an evanescent wave on the optical fiber surface to excite the photocatalyst. Unlike the excitation of conventional refracted light, the part of the refracted light not utilized by the catalyst will be dissipated into the reaction solution, while the evanescent wave energy not utilized by the catalyst can continue to propagate along the optical fiber, thereby improving the unevenness of light distribution and increasing the utilization rate of catalyst light.

[0029] 3. Due to the small diameter of the photocatalytic tapered optical fiber, the optical fiber can be easily coupled with a microfluidic reactor to improve reaction conditions such as mass transfer or integrate sensing functions, further realizing micro-efficient reactions or in-situ monitoring of the photocatalytic reaction process. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:

[0031] Figure 1 It is a schematic diagram of the structure of the photocatalytic tapered optical fiber of the present invention;

[0032] Figure 2 This is a schematic diagram of the incident light-excited photocatalyst of the present invention;

[0033] Figure 3: are numerical simulation analysis diagrams of the embodiments of the present invention and the comparative examples, wherein a is a schematic diagram of the optical fiber structure of the comparative example, which refers to a photocatalytic cylindrical optical fiber without tapering treatment; b is a schematic diagram of light propagation of the comparative example; c is a schematic diagram of the optical fiber structure of the embodiment, which refers to a photocatalytic tapered optical fiber obtained by thermal stretching treatment; d is a schematic diagram of light propagation of the embodiment;

[0034] Figure 4 The SEM images of the comparative example and Example 1 of the present invention, wherein a is a photocatalyst coating loading effect image of the comparative example; b is a photocatalyst coating loading effect image of Example 1;

[0035] Figure 5 This is a comparison chart of the reflection times of light incident at different angles between the comparative example of the present invention and Example 1;

[0036] Figure 6 It is a comparison chart of hydrogen production rate per unit mass of catalyst in comparative example and embodiment of the present invention.

[0037] In the figure: 1 – input part; 2 – tapered part; 3 – photocatalyst coating; 4 – light input end. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0039] The present invention discloses a photocatalytic tapered optical fiber, in which a photocatalyst is loaded on a tapered portion where the diameter of the optical fiber is reduced, so as to enhance the number of light reflections in a photocatalytic reaction region, make the light energy distribution in the region more concentrated, and simultaneously regulate the distribution of the photocatalyst, thereby improving the problem that the photocatalyst distribution and the light distribution of an optical fiber photocatalytic reactor cannot be perfectly matched, and improving the hydrogen production performance of the photocatalyst per unit mass.

[0040] See also Figure 1 A photocatalytic tapered optical fiber comprises an input portion and a tapered portion with a gradually decreasing optical fiber diameter, wherein the tapered portion is provided with a photocatalyst coating. The optical fiber is subjected to heat stretching treatment to form a tapered portion with a gradually decreasing optical fiber diameter at one end, and the optical fiber end that has not been subjected to heat stretching treatment is the input portion, and the end of the input portion away from the tapered portion is recorded as the light input end, and the tapered portion is used as a photocatalytic reaction area, and the photocatalytic reaction area is also understood as the tapered area end of the optical fiber with a gradually decreasing diameter and a photocatalyst coating.

[0041] The light input end is connected to a light source so that light enters the optical fiber for propagation. The tapered portion is immersed in a reaction solution. The photocatalyst coating contacts the reaction solution and undergoes a photocatalytic water decomposition reaction to produce hydrogen after being excited by light.

[0042] A method for preparing a photocatalytic tapered optical fiber, the specific steps are as follows:

[0043] Step 1. Thioacetamide (0.025-0.03 mol) was added to an aqueous solution of Cd(Ac)2*2H2O and Zn(Ac)2*2H2O (n(Cd)+n(Zn)=0.02 mol) under magnetic stirring, and the mixture was further stirred for 15-20 minutes;

[0044] Step 2. The mixed solution is sealed in a polytetrafluoroethylene-lined stainless steel autoclave and heated to 160-180°C for 24-26 hours. After cooling, the product is separated by centrifugation, washed with deionized water and ethanol for 3-5 times, and dried in a vacuum oven at 60-80°C for 5-6 hours to obtain Cd 0.5 Zn 0.5 S powder sample;

[0045] Step 3. Take a 30-50cm long optical fiber, use a wire stripper to strip off the coating of 3-5cm in the middle area, wipe it clean with alcohol cotton, and clamp the two ends of the optical fiber on the two sliders of the guide rail. Fix one of the sliders and slide the other slider to make the clamped optical fiber slightly taut.

[0046] Step 4. Use a flame spray gun to burn the area where the coating is stripped off. After burning into a molten state, one end of the slider is fixed and the other end of the slider is pulled outward at a constant speed to stretch the optical fiber from the burned area until it breaks, forming a tapered structure; the diameter of the tapered part is reduced from 62.5-125μm to 7-10μm, and the length of the tapered part is 0.7-10mm;

[0047] Step 5. Use the Cd obtained in step 2 0.5 Zn 0.5 S powder and deionized water are prepared into a 0.2-10g / L suspension, and ultrasonic and stirring are used to make it evenly dispersed. The tapered part of the tapered optical fiber obtained in step 4 is immersed in the suspension for 5-15 minutes, then air-dried for 1-2 hours, and then heated at 150-200°C for 1-2 hours to obtain a photocatalytic tapered optical fiber.

[0048] The photocatalyst coating occupies 20% to 100% of the surface area of ​​the tapered portion of the optical fiber, and the coating thickness is 100 to 500 nm.

[0049] like Figure 2As shown, since the refractive index of the photocatalyst coating is higher than that of the optical fiber, the light propagating in the optical fiber will be refracted and excite the photocatalyst in the form of refracted light when it is reflected at the contact surface between the photocatalyst and the optical fiber; when the light is reflected on the surface of the optical fiber without direct contact with the photocatalyst, an evanescent wave is generated in the form of total reflection to excite the photocatalyst near the reflection point; by adjusting the concentration of the photocatalyst suspension during the preparation process, the distribution of the catalyst on the optical fiber surface can be controlled so that it fully or partially covers the optical fiber surface.

[0050] If the photocatalyst coating completely covers the surface of the tapered optical fiber, light will only excite the photocatalyst in the form of refracted light; if the photocatalyst coating does not completely cover the surface of the tapered optical fiber, light will excite the photocatalyst in the form of refracted light and evanescent waves. If the refracted light energy is not fully utilized by the catalyst, the remaining energy will be dissipated into the reaction solution, and if the evanescent wave energy is not fully utilized by the catalyst, it can return to the optical fiber and continue to propagate forward, and be absorbed and utilized by subsequent catalysts.

[0051] Example 1

[0052] This embodiment prepares the photocatalytic tapered optical fiber according to the following steps:

[0053] Step 1. Thioacetamide (0.025 mol) was added to an aqueous solution of Cd(Ac)2*2H2O and Zn(Ac)2*2H2O (n(Cd)+n(Zn)=0.02 mol) under magnetic stirring, and the mixture was further stirred for 15 minutes;

[0054] Step 2. The mixed solution was sealed in a polytetrafluoroethylene-lined stainless steel autoclave and heated to 180°C for 24 hours; after cooling, the product was separated by centrifugation, washed with deionized water and ethanol for 4 times, and dried in a vacuum oven at 80°C for 5 hours to obtain Cd 0.5 Zn 0.5 S powder sample;

[0055] Step 3. Take a 40cm long optical fiber (the optical fiber is a coreless optical fiber with a diameter of 125μm and a refractive index of 1.444), use a wire stripper to strip off the coating layer of the middle area of ​​3cm, wipe it clean with alcohol cotton, and clamp the two ends of the optical fiber on the two sliders of the guide rail respectively, fix one of the sliders, and slide the other slider to make the clamped optical fiber in a slightly tight state;

[0056] Step 4. Use a flame spray gun to burn the area where the coating is stripped off. After burning into a molten state, fix one end of the slider and pull the other end of the slider outward at a constant speed to stretch the optical fiber from the burned area until it breaks, forming a tapered structure.

[0057] Step 5. Use the Cd obtained in step 2 0.5 Zn 0.5S powder and deionized water were prepared into a 1 g / L suspension, and ultrasonic and stirring were used to make it evenly dispersed. The tapered part of the tapered optical fiber obtained in step 4 was immersed in the suspension for 10 minutes, then air-dried for 1 hour, and then heated at 200°C for 1 hour to obtain a photocatalytic tapered optical fiber.

[0058] Combined with the measurement of optical microscope, it was found that the length of the tapered portion of the photocatalytic tapered optical fiber was 7.5 mm.

[0059] Example 2

[0060] This embodiment prepares a photocatalytic tapered optical fiber in the same manner as in Embodiment 1, and still uses a 125 μm coreless optical fiber for the tapering process. The difference is that the tapered portion of the tapered optical fiber after the tapering process in this embodiment has a length of 700 μm, and the reaction length is shorter.

[0061] Comparative Example

[0062] This comparative example prepares a photocatalytic optical fiber according to the following steps, which is different from Example 1 in that the optical fiber is not subjected to a taper treatment by thermal stretching.

[0063] Step 1. Thioacetamide (0.025 mol) was added to an aqueous solution of Cd(Ac)2*2H2O and Zn(Ac)2*2H2O (n(Cd)+n(Zn)=0.02 mol) under magnetic stirring, and the mixture was further stirred for 15 minutes;

[0064] Step 2. The mixed solution was sealed in a polytetrafluoroethylene-lined stainless steel autoclave and heated to 180°C for 24 hours; after cooling, the product was separated by centrifugation, washed with deionized water and ethanol for 4 times, and dried in a vacuum oven at 80°C for 5 hours to obtain Cd 0.5 Zn 0.5 S powder sample;

[0065] Step 3. Take a 40cm long optical fiber (the optical fiber is a coreless optical fiber with a diameter of 125μm and a refractive index of 1.444), use a wire stripper to strip off the 3cm coating at one end of the optical fiber, and wipe it clean with alcohol cotton;

[0066] Step 4. Use the Cd obtained in step 2 0.5 Zn 0.5 S powder and deionized water were mixed into a 1 g / L suspension, and ultrasonic and stirring were used to make it evenly dispersed. The end of the optical fiber obtained in step 4 with the coating removed was immersed in the suspension for 10 minutes, air-dried for 1 hour, and then heated at 200°C for 1 hour to obtain a photocatalytic optical fiber.

[0067] Step 5. Use a fiber optic cutting knife to cut the photocatalytic optical fiber so that the length of the optical fiber segment with the photocatalyst coating is consistent with that in Example 1.

[0068] like Figure 3 As shown, the light propagation of the embodiment and the comparative example at the same reaction length was numerically simulated. The embodiment and the comparative example in the figure can be regarded as the embodiment 1 and the comparative example when the optical fiber surface is fully covered by the photocatalyst. At this time, all the light is released to the photocatalyst in the form of refracted light. It can be seen that the light energy released to the photocatalyst in the comparative example and the embodiment gradually decays along the light propagation direction, but in embodiment 1, the light energy release in the tapered area of ​​the optical fiber is more intensive and concentrated.

[0069] Depend on Figure 4 Specific information on the optical fiber structural parameters and catalyst distribution of the comparative example and Example 1 can be obtained. The comparative example optical fiber has not been tapered, and the optical fiber diameter remains unchanged at 125 μm; the diameter of the tapered portion of the optical fiber in Example 1 gradually decreases from 125 μm to 8 μm, and the distribution of the catalyst on the optical fiber surface in the comparative example and Example 1 is basically consistent. SEM characterization shows that the proportion of the catalyst occupying the optical fiber surface area of ​​both is 27%, and the coating thickness is 103 nm.

[0070] Figure 5 The number of light reflections at different angles of Example 1 and the comparative example are compared. It can be seen that after the tapering process, the number of light reflections of Example 1 is significantly improved compared with the comparative example.

[0071] The comparative example and example optical fibers obtained according to the above steps were subjected to a photocatalytic hydrogen production test under a 370nm LED light source and other identical experimental conditions, and the hydrogen production effect was obtained, as shown in FIG. Figure 6 In Example 2, since the amount of catalyst used in the reaction area is too small, it is difficult to effectively detect the hydrogen production. Four tapered optical fiber samples are selected to connect to four LED light sources for joint reaction, and finally converted into hydrogen production data of a single optical fiber and a single light source for joint comparison.

[0072] Depend on Figure 6 It can be seen that the hydrogen production per unit mass of the catalyst in the embodiment is significantly improved compared with the non-tapered optical fiber. There is no significant difference between Example 1 and Example 2. Figure 3 , Figure 5 and Figure 6 It can be explained that the photocatalytic tapered optical fiber prepared by the present invention has a greatly increased number of light reflections in the tapered portion, and the light energy distribution is more concentrated, which can improve the problem that the photocatalyst distribution and light distribution of the optical fiber photocatalytic reactor cannot perfectly match each other, and improve the hydrogen production performance of the unit mass of the photocatalyst.

[0073] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.

Claims

1. A photocatalytic tapered optical fiber, characterized in that: The optical fiber comprises an input portion and a tapered portion where the diameter of the optical fiber gradually decreases, and the tapered portion is provided with a photocatalyst coating.

2. The photocatalytic tapered optical fiber according to claim 1, characterized in that: The maximum diameter of the tapered portion is 62.5-125 μm, the minimum diameter of the tapered portion is 7-10 μm, and the length of the tapered portion is 0.7-10 mm.

3. The photocatalytic tapered optical fiber according to claim 1, characterized in that: The photocatalyst coating has a thickness of 100-500 nm and occupies 20%-100% of the surface area of ​​the tapered optical fiber.

4. The photocatalytic tapered optical fiber according to claim 1, characterized in that: The photocatalyst in the photocatalyst coating is a semiconductor photocatalyst, preferably a sulfur-zinc-cadmium photocatalyst material Cd 0.5 Zn 0.5 S.

5. A method for preparing the photocatalytic tapered optical fiber according to any one of claims 1 to 4, characterized in that: The specific steps are as follows: S1, performing a taper process of thermally stretching the optical fiber to obtain a tapered optical fiber having an input portion and a tapered portion with a gradually decreasing optical fiber diameter; S2. Prepare a photocatalyst suspension, and load the photocatalyst coating on the tapered portion of the tapered optical fiber obtained in step S1 by a physical impregnation method to obtain a photocatalytic tapered optical fiber.

6. The preparation method according to claim 5, characterized in that: In step S1, the specific steps of the hot-stretching taper process are: (1) Take a 30-50 cm long optical fiber, peel off the coating layer of 3-5 cm in the middle area, wipe it clean with alcohol cotton, and clamp the two ends of the optical fiber on the two sliders of the guide rail. Fix one of the sliders and slide the other slider to make the clamped optical fiber slightly taut. (2) The area where the coating is stripped off is burned and molten. One end of the slider is fixed and the other end of the slider is pulled outward at a constant speed to stretch the optical fiber from the burned area until it breaks, forming a tapered structure.

7. The preparation method according to claim 5, characterized in that: In step S2, the concentration of the photocatalyst suspension is 0.2-10 g / L, and the Cd 0.5 Zn 0.5 S powder and deionized water to prepare, in which Cd 0.5 Zn 0.5 The preparation process of S powder is: a. Add thioacetamide to an aqueous solution of Cd(Ac)2*2H2O and Zn(Ac)2*2H2O under magnetic stirring, and stir the mixture for 15-20 min; wherein n(thioacetamide) / (n(Cd)+n(Zn)=(0.025-0.03):0.02; b. The mixed solution obtained in step a is sealed in a reaction kettle and heated to 160-180°C for 24-26 hours; after cooling, the product is separated by centrifugation, washed with deionized water and ethanol for 3-5 times, and dried in a vacuum oven at 60-80°C for 5-6 hours to obtain Cd 0.5 Zn 0.5 S powder sample.

8. The preparation method according to claim 5, characterized in that: In step S2, the specific process of the physical immersion method is: immersing the tapered portion of the tapered optical fiber in the photocatalyst suspension for 5-15 minutes, air-drying for 1-2 hours, and then heating at 150-200°C for 1-2 hours.

9. Application of the photocatalytic tapered optical fiber according to any one of claims 1 to 4 in photocatalytic water decomposition to produce hydrogen, wherein the light source enters through the input portion and eventually propagates to the tapered portion immersed in the reaction solution to excite the photocatalyst coating to generate a photocatalytic reaction.

10. The use according to claim 9, characterized in that: The light source is an LED light source or a laser light source with a wavelength range of 365-600nm; The reaction solution is a photocatalytic sacrificial reagent, and the photocatalytic sacrificial reagent includes any one of a mixed solution of sodium sulfite and sodium sulfide, methanol, lactic acid, and triethanolamine.

Citation Information

Patent Citations

  • Photocatalyst, preparation method thereof, photocatalyst system and application

    CN114192167A

  • Three-dimensional maple leaf micro-nano flower Cd0. 8Zn0. 2S photocatalyst and preparation method thereof

    CN117163998A

  • Microchannel reactor for photocatalytic decomposition of water to produce hydrogen by optical fiber conical tip condensation, and preparation method and application thereof

    CN117323944A